KIR4.1: K+ Channel Illusion or Reality in the Autoimmune Pathogenesis of Multiple Sclerosis - Gu, Chen (Frontiers in Molecular Neuroscience, 2016)
Multiple sclerosis (MS) is an inflammatory demyelinating disease of the central nervous system (CNS). Many believe autoimmune pathogenesis plays a key role in MS, but its target(s) remains elusive. A recent study detected autoantibodies against KIR4.1, an ATP-sensitive, inward rectifier potassium channel, in nearly half of the MS patients examined. KIR4.1 channels are expressed in astrocytes. Together with aquaporin 4 (AQP4) water channels, they regulate astrocytic functions vital for myelination. Autoantibodies against AQP4 have been established as a key biomarker for neuromyelitis optica (NMO) and contributed to diagnostic and treatment strategy adjustments. Similarly, identification of KIR4.1 autoantibodies could have high therapeutic values in treating MS. Consistent with its potential role in MS, KIR4.1 dysfunction is implicated in several neurological disorders. However, the enrichment of KIR4.1 autoantibodies in MS patients is questioned by follow-up studies. Further investigations are needed to clarify this controversy and unravel the underlying mechanisms of MS pathogenesis.